2006
DOI: 10.1097/00001665-200603000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Pindborg Tumor in Children

Abstract: Pindborg tumor or calcifying epithelial odontogenic tumor is a rare benign neoplasm. The average age at diagnosis is 40 years without a significant prevalence for one sex. The most frequent localization is the mandibular premolar and molar area; less frequently the lesion is found in the maxilla, while other localizations like the maxillary sinus are extremely rare. Ethiology of this lesion is not clear. The complete surgical removal of the lesion is usually considered the most common type of treatment. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…3 The study patient underwent hemimandibulectomy and no recurrence was reported in 6 months of follow up.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…3 The study patient underwent hemimandibulectomy and no recurrence was reported in 6 months of follow up.…”
Section: Discussionmentioning
confidence: 84%
“…2,3 Local recurrence rates of 10-15% have been reported and malignant transformation is rare. 3 Etiology of this lesion is not clear. Majority of the investigators are of the opinion that, the tumour cells originate from the striatum intermedium of the normal dental lamina.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic differential diagnoses include odontogenic myxoma, calcifying odontogenic cyst, complex odontoma, ameloblastic fibro-odontoma, fibro-osseous lesion and osteoblastoma. In the reported pediatric cases, the radiographic differential diagnoses included aneurysmal bone cyst, ameloblastoma, odontogenic keratocyst and dentigerous cyst [1, 515]. Although identifying the pathological entity based on radiological findings alone can be challenging, the overall tumor size, location and extension are important radiological clues for devising a plan for surgical intervention [19, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…CEOT most commonly occurs in individuals between 20 and 60 years of age, with peak incidence in the 5th decade; however a wide age range from 8 to 92 years has been reported [1, 3]. To date, about 200 cases have been reported [4], of which only 14 cases including the present case occurred in children [1, 515]. Although this tumor does not show a gender predilection, 71% of the cases reported in children have been seen in females (Table 1).…”
Section: Introductionmentioning
confidence: 97%
“…A case report and literature review by Fazeli et al outlined 14 cases of CEOT in pediatric patients, with only 4 occurring in the maxilla; 7 Ungari et al performed enucleation and curettage of a 0.8 cm CEOT of the maxilla in a 9-year-old boy; 8 Mopsik et al documented intra-oral access and enucleation for a cystic CEOT of the maxilla in a 13-year-old girl; 9 Gopalakrishnan et al reported a large invasive cystic CEOT situated within the maxillary sinus itself which was enucleated via Caldwell-Luc approach; 10 and Mandal et al described a 6 x 5 cm CEOT of the hard palate causing lytic changes in adjacent bony structures, although the type of excision was unspecified. 11 No recurrence was documented for any of these cases, but follow-up periods for these cases ranged only from 1 month to 1 year.…”
mentioning
confidence: 99%